Reforms in Long-Term Care Policies in Europe Investigating Institutional Change and Social Impacts - Ranci, Costanzo; Pavolini, Emmanuele; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Reforms in Long Term Care Policies in Europe describes and interprets the changes recently introduced in long-term care policies in Western Europe. The volume argues that recent reforms have brought about an increasing convergence in LTC policies across Western Europe. Most of the new programs have developed a new general approach to long-term care, based on a better integration of social care and health care. Over the last two decades, many changes have happened to the social welfare policies of various industrial countries. Citizens have seen their pensions, unemployment benefits, and general healthcare policies shrink as (3z(Bbelt tightening(3y (Bmeasures are enforced. But in contrast, long-term care has seen a general growth in public financing, an expansion of beneficiaries, and, more generally, an attempt to define larger social responsibilities and related social rights. The book explores increasing public support given to family care work (in the past, the family would take care of the elderly or infirm) and increasing growth and recognition of a extended social care market (by which care has shifted from a moral obligation based on family reciprocity to a paid, professional activity). A new social care arrangement has therefore been developing in Western countries, based on a new mix of family obligations, market provision, and public support. In order to understand such changes, the analysis in Reforms in Long Term Care Policies in Europe will take into account the social and economical impact of these reforms. Reforms in Long Term Care Policies in Europe is a great resource for health-care practitioners, demographers, public policy makers, public health scientists, gerontologists, researchers in health care management, and anyone interested in the impact of aging on societies.s
Keywords: Social sciences; Geriatrics; Public health; Social policy; Aging -- Research; Social Sciences; Aging; Public Health; Social Policy; Geriatrics/Gerontology.